The relationship between mindfulness and self-acceptance of families who have family members with mental disorders in RSKD Dadi Sul-Sel Province - Paseno, Matilda M.; Bara’, Yunis Meilin; Rosdiana, Meyke (Institute of Computer Science (IOCS), 2024)
Self-acceptance is a person's ability to accept the strengths and weaknesses of himself and his family members who are diagnosed with mental disorders. Self-acceptance can occur if there is mindfulness or full awareness of a person of the experience being experienced without blaming the condition or judging oneself. The purpose of this study was to determine whether there is a relationship between mindfulness and self-acceptance of families who have family members with mental disorders at Dadi Mental Hospital, South Sulawesi Province. The type of research used is quantitative with analytical observational methods with a cross sectional study approach. The sampling technique was non-probability sampling with a consecutive sampling approach. Data collection using a questionnaire research instrument. Data analysis using the chi-square test read on the person chi-square and obtained a value of p = 0.00 and α = 0.05 so that p <α then the alternative hypothesis (Ha) is accepted and hypothesis 0 (H0) is rejected. This shows that there is a relationship between mindfulness and self-acceptance of families who have family members with mental disorders at Dadi Mental Hospital, South Sulawesi Province, which means that mindfulness can affect a person's self-acceptance.